THE EFFECT OF FINANCIAL STABILITY, EXTERNAL PRESSURE AND FINANCIAL TARGET ON FINANCIAL STATEMENT FRAUD IN BUMN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2022 - Olivia, Valeria Putri; Rispantyo , Rispantyo (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study to determine the effect of Financial Stability External Pressure and Financial Target on Financial Statement Fraud which is proxied by F- Score. The proxied of each variable are ratio change of total asset (ACHANGE), Debt to Asset Ratio (DAR) and Return on Asset (ROA). The data is secondary data. Population in this study is BUMN Companies that listed on Indonesia Stock Exchange (BEI). The research sample consisted of 14 companies using purposive sampling. Hypothesis testing used multiple linear analysis by using of SPSS 25 software application. The results of this study indicate that Financial Stability had no effect on Financial Statement Fraud, negatif significant on External Pressure and Positif significant on Financial Target